Mould design and mechanical analysis of the casted material - Mohd Azuan, Abu Shah (2010)
This report is an outcome of the work carried out in doing and completing final year project, mould design and mechanical analysis of the casted material. Objectives of this project is to design and fabricate the mould for tensile test specimen, following ASTM E8 standard and to study the mechanical properties of the casted materials and its comparison with effect of the cooling rate between water, oil and air. Materials that have been used for mould is mild steel and for casted material is aluminum alloy. Overall, this project was run based on four main steps; design using Solid Work, running a simulation on Master CAM, fabricated using CNC Milling Machine, and finally casting process. Each sample was then tested by Rockwell hardness in order to study the effect of the cooling media to the hardness of casted material for all three cooling media, water, oil and air. It project was done by testing at the outer surface and inner surface of the casted aluminum alloys. The higher value for outer surface hardness test is 49.10 HRB and the higher value for inner surface hardness test is 37.72 HRB. The result shows the hardness of casted material immersed in water has higher value compared to oil and air. Water has proved to be the best mediums for cooling rate compare to oil and air medium. The hardness of aluminium increases with the increasing of cooling rate. Cooling rate decreases with distance from the quenched end, and the hardness also decreases.